2002
DOI: 10.1103/physrevb.65.115411
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-inducedp(2×3)reconstruction on Mo(112) studied by LEED and STM

Abstract: The open trough-and-row Mo͑112͒ surface serves as substrate for the epitaxial growth of MoO 2 . In the early stage of oxygen exposure, oxygen chemisorption induces a p(2ϫ3) surface reconstruction of the missing row type on Mo͑112͒. The surface structure of this reconstructed surface has been studied in detail by low-energy electron diffraction and scanning tunneling microscope. The experimental findings can be explained based on the effective medium theory for oxygen adsorption on transition-metal surfaces, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…A p(1×3) phase is present for 35 L followed by a continuous transition to the p(2×3) phase. The emerging [h+ 1 2 α] streaks (h integer numbers and α almost continuous) were attributed to a high amount of antiphase domain boundaries [48,49,56,81]. The dosage for achieving specific superstructures is about a factor of 2 higher than in Ref.…”
Section: A Superstructure Phasesmentioning
confidence: 84%
“…A p(1×3) phase is present for 35 L followed by a continuous transition to the p(2×3) phase. The emerging [h+ 1 2 α] streaks (h integer numbers and α almost continuous) were attributed to a high amount of antiphase domain boundaries [48,49,56,81]. The dosage for achieving specific superstructures is about a factor of 2 higher than in Ref.…”
Section: A Superstructure Phasesmentioning
confidence: 84%
“…A (2x3) reconstructed surface was first observed by Schroeder et al in the course of the preparation of thin silica films on Mo(112) [15][16]. The authors suggested the (2x3) surface to be a precursor to the formation of an epitaxial MoO 2 film [17][18].…”
Section: Introductionmentioning
confidence: 91%
“…For the (2x3) surface, the authors proposed another, more stable structur e where the oxygen atoms occupy only quasi-threefold hollow sites, and suggested that the structure proposed by Schroeder et al [17] is metastable. However, the authors did not consider the effect of oxygen partial pressure on the stability of different structures and assumed the same oxygen content as in the Schroeder at al's model.…”
mentioning
confidence: 99%
“…While a (3×1) or (3×3) reconstruction has previously been reported during oxidation of the W(100) surface [5], it is not so commonly observed as on the closely similar Mo(100) and Ta(100) surfaces [18][19][20]. During oxidation of the Mo(112) surface, p(2×3) and p(1×3) missing-row reconstructions have been identified as precursors to the formation of an epitaxial MO 2 layer [21][22][23]. In the present case, the nucleation of a penetrated oxide WO x is also observed at the boundaries between orthogonal domains of the p(3×1) reconstruction.…”
Section: Introductionmentioning
confidence: 98%